HAEMOTHERAPY ANALYSIS: THE TEACHING HOSPITAL OLOMOUC IN 2006 - Galuszkova, Dana; Galuszka, Jan (Biomedical papers, 2007)
Aims: Annual evaluation of blood transfusion preparation administration at the University Hospital Olomouc, Czech Republic as a contribution to the European Union haemovigilance system.Methods: Analysis of blood transfusion preparations released from the Department of Blood Transfusion of the above university hospital and laboratory examination results in receivers of these products for the year 2006. Total hospital consumption and usage in particular medical disciplines in the hospital were assessed.Results: Red cell concentrates: in total 14 347 TU (deleucotised in 20.4 %). Departments according to usage: surgery, haematooncology, anaesthesiology and surgery intensive care department, and internal medicine department. Haemoglobin levels were above 100 g/L before blood transfusion administration in 24 % of cases. Platelets: in total 1 712 TU (100 % manufactured by apheresis, 56 % deleucotised). Platelet counts below 20 x 109/L were found in all cases before platelet concentrate administration. Plasma: in total 5 959 TU to 1 297 of patients. Departments according to usage: surgery, anaesthesiology and surgery intensive care department, internal medicine and haematooncology. Two hundred and forty nine cases without coagulation parameter monitoring and 333 (25.67 %) patients with only 1 TU of administered plasma were found.Conclusions: The incorrect indications for red cell transfusion preparations were found in eleven patients with haemoglobin levels above 130 g/L. Underdosing in 25.67 % of plasma administrations signifies dubious indications in these cases. Implementation of the haemovigilance system in practice is now mandatory for the Czech Republic after joining the European Union. Therefore more precise data and analysis of questionable cases with further education of staff in clinical departments are essential for the haemovigilance principle to be applied on a hospital basis in the Czech Republic.
Keywords: Haemotherapy/Blood transfusion/Haemovigilance